Incomplete IgG avidity maturation after seasonal coronavirus infections. Issue 1 (27th August 2021) - Struck, Friedhelm; Schreiner, Patrick; Staschik, Eva; Wochinz‐Richter, Karin; Schulz, Sarah; Soutschek, Erwin; Motz, Manfred; Bauer, Georg
Abstract: In classical viral infections, the avidity of immunoglobulin G (IgG) is low during acute infection and high a few months later. As recently reported, SARS‐CoV‐2 infections are not following this scheme, but they are rather characterized by incomplete avidity maturation. This study was performed to clarify whether infection with seasonal coronaviruses also leads to incomplete avidity maturation. The avidity of IgG toward the nucleoprotein (NP) of the seasonal coronaviruses 229E, NL63, OC43, HKU1 and of SARS‐CoV‐2 was determined in the sera from 88 healthy, SARS‐CoV‐2‐negative subjects and in the sera from 70 COVID‐19 outpatients, using the recomLine SARS‐CoV‐2 assay with recombinant antigens. In the sera from SARS‐CoV‐2‐negative subjects, incomplete avidity maturation (persistent low and intermediate avidity indices) was the lowest for infections with the alpha‐coronaviruses 229E (33.3%) and NL63 (61.3%), and the highest for the beta‐coronaviruses OC43 (77.5%) and HKU1 (71.4%). In the sera from COVID‐19 patients, the degree of incomplete avidity maturation of IgG toward NP of 223E, OC43, and HKU1 was not significantly different from that found in SARS‐CoV‐2‐negative subjects, but a significant increase in avidity was observed for IgG toward NP of NL63. Though there was no cross‐reaction between SARS‐CoV‐2 and seasonal coronaviruses, higher concentrations of IgG directed toward seasonal coronaviruses seemed to indirectly increase avidity maturation of IgG directed toward SARS‐CoV‐2. Our data show that incomplete IgG avidity maturation represents a characteristic consequence of coronavirus infections. This raises problems for the serological differentiation between acute and past infections and may be important for the biology of coronaviruses. HIGHLIGHTS: Immunoglobulin G (IgG) directed toward NP of seasonal coronaviruses shows incomplete avidity maturation The degree of incomplete avidity maturation is determined by the virus strain Incomplete avidity maturation is more prominent after infection with betacoronaviruses Incomplete avidity maturation of IgG against seasonal coronaviruses is independent of SARS‐CoV‐2 infection SARS‐CoV‐2 infections also lead to incomplete avidity maturation Incomplete avidity maturation might allow for secondary coronavirus infections Graphical abstract: